Economic Analysis for Achieving Allocative-Technical Efficiency in Sustainable Agricultural Projects (Calf Fattening Farm as A Model) - Abbas Abd Ahmed Al-Tamimi; Dawood Fahad Abdullah (Andalasian International Journal of Agriculture and Natural Sciences (AIJANS), 2025)
Livestock production projects are environmentally friendly, as they provide farmers with organic fertilizers and year-round job opportunities. This helps reduce the use of chemical fertilizers, thereby simultaneously achieving the goal of environmental improvement and poverty reduction. This research conducted an economic analysis of a calf fattening farm in Diyala Province for 2024. The research adopted a quantitative economic analysis methodology using a multivariate production function in the double logarithmic form. The research aimed to conduct a quantitative economic analysis to determine the optimal combination of production resources to achieve optimal production. Based on the prices of production resources, the cost equation was formulated, and then the Lagrange multiplier method was used to create the objective function. The optimal production reached (827) K.g/calf, which represents the weight of the calf during the fattening period of (25) weeks. The economic analysis showed that the elasticity of production resources was less than one, which means that the production process is in the second stage of the law of diminishing returns, where technical efficiency is achieved. Through the analysis of the allocative efficiency of production resources, it became clear that there is an inefficient use of dry fodder and green fodder, as the elasticity of these two resources was greater than one, and less than one for the other resources. The study recommended increasing the effective role of agricultural extension to educate calf farmers on the application of scientific research findings to achieve optimal production levels. It also recommended In addition to supporting fodder.